Синтез двухмассового электропривода с астатической системой подчиненного регулирования при действии переменных сил трения - Задорожняя, И.Н.; Задорожний, Н.А. (Електротехніка і електромеханіка, 2018)
Получил дальнейшее развитие метод синтеза электропривода с астатической системой подчиненного регулирования при действии переменных сил трения с активным демпфированием упругих механических колебаний, что достигается выбором определенного соотношения динамических параметров. Показано, что параметры в электромеханических системах находятся во взаимосвязи, а реализация расчетных соотношений для регулятора скорости при оптимизации основана на компенсации влияния упругих сил инерционными и может быть использована для настройки систем управления технологических машин. Отримав подальший розвиток метод синтезу електроприводу з астатичною системою підпорядкованого регулювання при дії змінних сил тертя з активним демпфіруванням пружних механічних коливань, що досягається вибором відповідного співвідношення динамічних параметрів. Показано, що параметри в електромеханічних системах знаходяться у взаємозв’язку, а реалізація розрахункових співвідношень для регулятора швидкості при оптимізації основана на компенсації впливу пружних сил інерційними та може бути використана для настройки систем керування технологічних машин. Purpose. The solution of actual problem of active suppression of resilient electromechanical vibrations in an electric drive with the astatic system of automatic control is presented. Methodology. For research of damping properties of electrical drive according to a flow diagram from transmission functions on regulation and indignation a characteristic polynomial is got in the rationed form of parameters that takes into account the physical phenomena and sets intercommunications of parameters in the electromechanical system. As a result of it a characteristic polynomial at a successive dynamic decoupling appears separate interactive electromagnetic and mechanical subsystems. Thus, electromechanical interaction physically means complete extraction of energy of vibrations from a mechanical subsystem in electromagnetic with simultaneous transformation for minimum time. An electric drive for the case of realization of processes of electromechanical interaction is the dynamic extinguisher of vibrations. Results. The active resilient mechanical oscillation damping comes true due to optimization of dynamic inflexibility of mechanical description of electrical drive and as a result the required degree of stability is provided at minimum vibration and high exactness of working off indignations on loading. Originality. For the first time an electrical drive with the astatic system of automatic control at the action of variable forces of friction for the offered optimal parameters of dynamic inflexibility of mechanical description effectively damps vibrations. The synthesis of parameters of regulators according to correlations allowed to realize the maximum indexes of character of attenuation processes at a zero static error. Practical value. The synthesis method is approved in industrial conditions during the adjustment and modernization of the machine tool and is recommended for setting up automatic control systems for the operating and newly designed electric drives of technological machines.